2002
DOI: 10.1007/s00268-002-5958-8
|View full text |Cite
|
Sign up to set email alerts
|

How to pass on expertise: Pancreatoduodenectomy at a teaching hospital

Abstract: Pancreatoduodenectomy (PD) has become a routine procedure. Recent series report perioperative mortality rates of 5% or less, moderate morbidity, and even improved long-term survival. Nevertheless, being one of the most complex abdominal operations, a certain number of surgical procedures (i.e., personal caseload) seems essential for acceptable results. The objectives of this retrospective study were to evaluate whether PD can be safely performed as a teaching operation, and if the personal caseload of the seni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Risk stratification of a POPF may have a role in facilitating training opportunities. A PD is considered one of the most technically demanding surgical procedures and is a challenging operation for both trainers to teach and trainees to learn . Recognizing patients at a lower risk of POPF may permit the trainee to perform the pancreatoenteric anastomosis, and conversely an experienced pancreatic surgeon may choose to construct this anastomosis in a high‐risk patient.…”
Section: Discussionmentioning
confidence: 99%
“…Risk stratification of a POPF may have a role in facilitating training opportunities. A PD is considered one of the most technically demanding surgical procedures and is a challenging operation for both trainers to teach and trainees to learn . Recognizing patients at a lower risk of POPF may permit the trainee to perform the pancreatoenteric anastomosis, and conversely an experienced pancreatic surgeon may choose to construct this anastomosis in a high‐risk patient.…”
Section: Discussionmentioning
confidence: 99%
“…Hepato-pancreato-biliary surgeons are needed in many surgical patients' experience [5]. Previous studies have shown the necessity for training in highvolume centers [4,18], under team medicine [24], or under the supervision of an experienced senior surgeon [25]. These suggestions are correct.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is caused predominantly by abdominal sepsis including sequelae like hemorrhage. Non-surgical, especially cardiopulmonary complications had been shown to add significantly to postoperative mortality and morbidity [15,17,18]. Percutaneous drainage is used to treat intraabdominal complications like fluid retention and abscesses due to pancreatic fistula, reoperation reserved for those situations, that cannot be controlled percutaneously.…”
Section: Perioperative Morbidity and Mortalitymentioning
confidence: 99%
“…Wamser et al were able to demonstrate that proctoring this complex procedure is possible in experienced centers without increased complication rates [15]. Some papers reported on the laparoscopic approach to pancreatic surgery and cancer.…”
Section: Reconstructionmentioning
confidence: 99%